2010
DOI: 10.1002/ajpa.21212
|View full text |Cite
|
Sign up to set email alerts
|

A genetic analysis of the Sakishima islanders reveals no relationship with Taiwan aborigines but shared ancestry with Ainu and main‐island Japanese

Abstract: The Sakishima islands are members of the Ryukyu island chain, stretching from the southwestern tip of the Japanese archipelago to Taiwan in the East China Sea. Archaeological data indicate cultural similarities between inhabitants of prehistoric Sakishima and Neolithic Taiwan. Recent studies based on tooth crown traits show remarkably high inter-island diversity among Ryukyu islanders, suggesting that the Sakishima islanders might have genetic backgrounds distinct from main-island Okinawa people. To investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 95 publications
4
44
0
Order By: Relevance
“…We found that two Sanganji individuals belonged to haplogroup M7a2 (Table 5, Table 7). In modern populations, haplogroup M7a1 was observed in modern Japanese populations at a high frequency: Ainu, 15.7% (Tajima et al, 2004); mainland Japanese, 9.5% (Maruyama et al, 2003); Ryukyuan, 26.6% (Horai et al, 1996, Matsukusa et al, 2010. However, haplogroup M7a2 was scarcely observed in the mainland Japanese (0.5%), and this haplogroup was not observed in the Ryukyuan.…”
Section: Population Comparison Based On Haplogroup Frequenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that two Sanganji individuals belonged to haplogroup M7a2 (Table 5, Table 7). In modern populations, haplogroup M7a1 was observed in modern Japanese populations at a high frequency: Ainu, 15.7% (Tajima et al, 2004); mainland Japanese, 9.5% (Maruyama et al, 2003); Ryukyuan, 26.6% (Horai et al, 1996, Matsukusa et al, 2010. However, haplogroup M7a2 was scarcely observed in the mainland Japanese (0.5%), and this haplogroup was not observed in the Ryukyuan.…”
Section: Population Comparison Based On Haplogroup Frequenciesmentioning
confidence: 99%
“…The primers used to amplify HVR-1, HVR-2, and haplogroupdetermining regions are listed in Table 2 and Table 3. Analyzed haplogroups were compared with those of modern Japanese and Jomon people (Horai et al, 1996;Shinoda and Kanai, 1999;Shinoda, 2003;Maruyama et al, 2003;Tajima et al, 2004;Tanaka et al, 2004;Adachi et al, 2008Adachi et al, , 2009aAdachi et al, , b, 2011Matsukusa et al, 2010). To further characterize the sub-haplogroups within N9 and M7a, we used additional primers listed in Table 4.…”
Section: Pcr Amplification and Sequencingmentioning
confidence: 99%
“…16 Mitochondrial DNA and Y chromosomal DNA examinations became popular for human population studies from the 1980s, and a series of papers were published for human populations of the Japanese Archipelago. [20][21][22][23][24][25][26][27][28] All of these studies showed some genetic similarity between the Ainu and the Ryukyuan populations. However, mitochondrial DNA and Y chromosomes are both non-recombining, and the genetic information that can be extracted is limited.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] However, these studies have mainly only used information on major haplogroups, and investigations based on more detailed haplogroup classification remain to be made because of the lack of suitable markers. Our group has already described the most detailed Y-chromosomal haplogroup classification in the Japanese population by expanding the YCC tree of 2003, assigning 5 new JSNP markers.…”
mentioning
confidence: 99%